Phytochemistry and Pharmacological Activities of Wolfiporia cocos (F.A. Wolf) Ryvarden & Gilb - Nie, Anzheng; Chao, Yanhui; Zhang, Xiaochuan; Jia, Wenrui; Zhou, Zheng; Zhu, Chunsheng (Frontiers in Pharmacology, 2020)
Abstract: Wolfiporia cocos (Schwein.) Ryvarden et Gilb., a widely used traditional Chinese medicine, is also called "Fuling" (Chinese:茯苓). Poria cocos has a long history, which was used to reduce phlegm and edema, treat nephrosis and chronic gastritis and relieve uneasiness of minds. Its extensive pharmacological effects have attracted considerable attention in recent years. However, there is no systematic review focusing on the chemical compounds and pharmacological effects of Poria cocos. Therefore, this review aimed to provide the latest information on the chemical compounds and pharmacological effects of Poria cocos, exploring the therapeutic potential of these compounds. To date, two main constituents, triterpenes and polysaccharides of Poria cocos, which have been identified from Poria cocos. Studies on the polysaccharides and triterpenes in the past decades, have been reported to have pharmacological effects on anti-tumour, anti-bacterial, anti-oxidant, anti-inflammatory, immunomodulation and liver and kidney protection. The review summarizes the phytochemistry and pharmacology properties of Poria cocos. And, These properties suggest that researchers should focus on the development of new drugs about Poria cocos to make Poria cocos exert greater therapeutic potential.